Menuju Ma’rifat dan Hakikat melalui Jihad dalam Menuntut Ilmu: Studi Syarah Hadis - Riki Muhammad Fahmi (Jurnal Riset Agama, 2021)
The purpose of this study is to examine the concept of studying in the perspective of hadith. This research method applies literature study and content analysis which are qualitative types. The results and discussion of this research include general views about studying, hadith about the command to study, and the virtues of studying according to hadith. This study concludes that the concept of studying according to the hadith includes the obligation to study general knowledge and sharia science to get to ma'rifat and essence in the form of an introduction to God which is aligned with jihad as a Muslim virtue that guarantees the life of the world and the hereafter.